Analisis Saluran Distribusi Sarana Produksi Pertanian (Saprotan) Pupuk di Kabupaten Pamekasan - Campina Illa Prihantini; Lutfiyanto Lutfiyanto (Fakultas Pertanian, Universitas Timor, 2019)
This research focuses on the distribution or distribution system of fertilizer production facilities (saprotan) in Pamekasan Regency. Agricultural production facilities are a major component that is important in the success of government programs in agriculture. Especially on the availability of fertilizers, both subsidized and non-subsidized fertilizers. This research was conducted in Pamekasan district by conducting enumeration activities on farm stalls and shops throughout Pamekasan Regency. The results of the enumeration activities show that the total number of kiosks, both official and non-official, is 313 kiosks. This amount is certainly very large, especially with the average number of kiosks of 24 kiosks per sub-district. Ironically, the problem of fertilizing fertilizers is still common, especially in terms of fertilizer availability during the growing season. This research is expected to be a basis for evaluation in determining the policy of the availability of fertilizer production facilities at the national level. This certainly has an impact on society, not only in agriculture, but also social, economic and health..